SAFETY AND EFFICACY OF THORACOSCOPIC LOBECTOMY IN PATIENTS WITH STAGE I NON-SMALL CELL LUNG CANCER - A. B. Ryabov (Sibirskij Onkologičeskij Žurnal, 2021)
Aim: to analyze short-and long-term treatment outcomes of thoracoscopic lobectomy in patients with stageI NSCLC .Material and Methods. A total of 479 NSCLC patients with clinical stage I NSCLC were treated at the Department of Thoracic Surgery of Hertzen Research Cancer Center from 2010 to 2019.Results. Conversion to thoracotomy was required in 62 (12.9 %) of patients. Postoperative complications occurred in 19.9 % of patients in the thoracoscopic group and in 25.8 % of patients in the conversion group: the mortality rates were 0.4 % and 1.6 % respectively. The most common complication was prolonged air-leak (>5 days), which was diagnosed in 11.9 % and 8.0 % of patients respectively. In patients aged >70 years, the rate of complications was 35.8 % in the thoracoscopic group and 41.2 % in the conversion group. Thoracoscopic lobectomy had advantages over thoracotomy in terms of less postoperative pain syndrome and much less decrease in FEV1 during the first postoperative days and months. In patients with pT1-2aN0M0, stage I NSCLC , the overall and disease-free 5-year survival rates were respectively 92.2 % and 86.6 % after thoracoscopic lobectomy and 87.5 % и 81.2 % after conversion.Conclusion. Thoracoscopic lobectomy is relatively safe procedure for patients with stage I NSCLC . To perform this type of surgery safely, the surgeon should pass the learning curve. Long-term outcomes were similar between patients undergoing thoracoscopic lobectomy and patients undergoing thoracotomy.